EVALUASI PENGGUNA JALAN TOL DI INDONESIA TERHADAP LAYANAN YANG DITERIMA - Amelia Makmur (Jurnal Jalan-Jembatan, 2021)
Toll road infrastructure has shown a significant number in recent years. This condition should be followed by operational service which meet the user expectations, in fact sometimes it doesn’t. A Minimum Service Standard (MSS) has already been set to ensure that users receive adequate services. However, users' needs and expectations are dynamic making it necessary to gather users' opinion and suggestion based on the available services. The aim of this research is to evaluate the service performance by exploring the opinions and expectations of toll road users regarding the service performance and the aspects of safety, security, and comfort regarding to MSS. This paper performed a survey by using online questionnaires, involving toll road users in Indonesia, on February 2018. The questionnaire results were then analyzed by using descriptive statistics. Results were shown that the users tend to 3 prioritize safety, then followed by security and comfort elements, respectively. The indicator of sufficient street lighting determines the fulfillment of MSS according to the perception of the users (1 from 18 indicators). This indicator has been included in the MSS. All indicators that affect users’ satisfaction have been found in MSS, except the indicator about ‘the availability of contacting the call center for users’ assistance’. Therefore, this paper suggest that the indicator mentioned in prior will be suggested to be in further consideration. Key words: Minimum Service Standard, safety, security, comfort, performance indicator